Human Papillomavirus (HPV): unawareness of the causal role of HPV infection in cervical cancer, HPV vaccine availability, and HPV vaccine uptake among female schoolteachers in a Middle Eastern country - Juman Rezqalla; Mariam Alshatti; Amna Ibraheem; Danah Omar; Al-Failakawi Houda; Shamayel AlHaqqan; Sarah AlGhurair; Saeed Akhtar (Journal of Infection and Public Health, 2021)
Background: Human papillomavirus (HPV) is the most common viral infection of the reproductive tract. This cross-sectional study among female schoolteachers assessed the prevalence of i) unawareness of HPV infection’s causal role in cervical cancer; ii) unawareness of HPV vaccine availability and iii) examined the sociodemographic variables associated both the outcome variables. Methods: This cross-sectional study was conducted among female schoolteachers employed in public and private sectors schools in Kuwait using a structured questionnaire for data collection. Prevalence of each of the outcome variables was computed. Multivariable logistic regression analyses were used to evaluate independent predictors of two dependent variables. Results: A total 1341 female schoolteachers were enrolled. Of the participants, 60% were unaware of HPV causal role in cervical cancer and 88% were unaware of HPV vaccine availability. Among those who were aware of HPV vaccine availability, 83.8% were unvaccinated. Multivariable logistic regression (MLR) model showed that 20–29 years old participants or those with low family income (< 500 KD/month) were significantly (p < 0.05) more likely to be unaware of HPV causal role in cervical cancer. Moreover, participants with family/ personal history of cervical cancer were significantly (p < 0.05) less likely to be unaware of HPV role in causation of cervical cancer. A separate MLR model revealed that the participants were significantly more likely to be unaware of HPV vaccine availability if they were Kuwaiti nationals or non-Kuwaiti Arabs (p < 0.05), employed in public schools (p = 0.003) or less likely to be unaware if they had personal or family history of cervical cancer (p < 0.001). Conclusion: High prevalences of unawareness of causal role of HPV in cervical cancer and unawareness of HPV vaccine availability were recorded. Targeted education among identified sociodemographic groups with high levels of unawareness is warranted. If undertaken, future studies may evaluate the impact of recommended efforts.